Effect of Penetrating Cryoprotectants and Low Temperature on Conformational State of Microsomal Proteins on UV-Spectrophotometry Data - Onischenko, E. V.; Dyubko, T. S. (Problems of Cryobiology and Cryomedicine, 2006)
Effect of penetrating low molecular cryoprotectants (CPs): glycerol, 1,2-propanediol (1,2-PD) and dimethyl sulfoxide (DMSO) as well the one of freeze-thawing with these cryoprotectants on conformational state of microsomal membrane proteins (MMP) derived from rats’ liver have been studied with UV-spectrophotometry. The efficiency of CPs interaction with MMP has been shown to depend both on their concentration and individual physical and chemical properties. The degree of CPs effect on MMP during freeze-thawing in greater extent depends on pre-sensibilization of microsomal membranes at the stage of their equilibration with CPs. Examined CPs on ascending of perturbing effect on MMP state could be disposed in the row: glycerol < 1,2 PD < DMSO.